UTILITY OF VALUE EDUCATION IN THE CURRENT EDUCATION SYSTEM - Kumar मुरारी; Pathak राम कुमार (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education is an important and universal subject. It is essential for human society. Education is the foundation of human development. Due to this educational development, human beings are the leader of all creatures in the world. It is because of education that human beings develop their sociality, wisdom, speech, creativity, and splendor. It is through education that the innate powers of human beings develop, as a result of which their knowledge and skills increase and their behavior changes. This process starts as soon as a human being is born. At the time of birth, the child is unaware of all the activities of the world. He is absolutely antisocial. But with time, as the child grows, he becomes more and more active. As he grows up, he comes in contact with family and society. Before going to school, the child has learnt a lot from the family and society. In the process of this learning, discipline and values ​​develop in the child. This systematic development process of learning and teaching continues inside and outside the school. It continues even after leaving school.